Cost-effectiveness of a telehealth intervention in rheumatoid arthritis: economic evaluation of the Telehealth in RA (TeRA) randomized controlled trial. (4th March 2023) - Skovsgaard, CV; Kruse, M; Hjollund, NHI; Maribo, T; de Thurah, A
Abstract : Objective: Telehealth is rapidly gaining ground from usual treatment, not least because of coronavirus disease 2019 (COVID-19) measures. Within rheumatology, telehealth has been used for, inter alia, follow-up for patients with rheumatoid arthritis (RA) with low disease activity or in remission. This study aims to assess the cost-effectiveness of such a telehealth intervention. Method: In a randomized controlled trial, 294 patients were randomized into patient-reported outcome-based telehealth follow-up by either a nurse (PRO-TN) or a rheumatologist (PRO-TR) or to conventional outpatient follow-up (control). Cost-effectiveness was evaluated using costs per quality-adjusted life-year (QALY) gained. Individual-level healthcare and productivity costs were retrieved from national Danish registers. Incremental cost-effectiveness ratios were calculated for the intervention groups compared to the control group. Bootstrapping with 10 000 replications was used to obtain confidence intervals. Furthermore, cost-effectiveness acceptability curves were generated. Results: The cost comparison showed that PRO-TR was significantly less costly than the control group, whereas the relative reduction in costs for PRO-TN was not significant. The telehealth groups experienced minor, non-significant declines in QALYs, whereas the control group experienced a slight, non-significant increase. The cost-effectiveness analysis showed that for PRO-TR, the willingness to accept a QALY loss was 89 328 EUR. A similar but smaller and non-significant result was seen for PRO-TN. Conclusion: PRO-TR and PRO-TN seem to cost less but provide broadly similar health outcomes compared with conventional follow-up. Between the intervention groups, PRO-TR was significantly less costly. More studies are needed to conclude whether rheumatologist- or nurse-led telehealth is more cost-effective than conventional follow-up.